The The Urgency of the Establishment of an Independent Supervisory in the Implementation of Article 58 of the Personal Data Protection Law in Indonesia - AH, Muh. Arfhani Ichsan; Anwar, Muh. Chaerul (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2026)
Digital transformation has increased the use of personal data along with the risks of data breaches and misuse. Indonesia has enacted Law Number 27 of 2022 concerning Personal Data Protection (PDP Law); however, its implementation remains ineffective due to the absence of a supervisory authority as mandated under Article 58 of the PDP Law. This study analyzes the impact of the absence of supervisory authority on the effectiveness of personal data protection and the obstacles to its establishment. This research employs a normative legal method and comparative approaches. The findings reveal that the absence of a supervisory authority results in weak oversight, low compliance among data controllers, and inadequate protection of data subjects’ rights. Establishing an authority also faces institutional challenges, overlapping powers, limited resources, and low awareness of data protection culture. Therefore, an independent supervisory authority is urgently needed to strengthen the implementation of the PDP Law in Indonesia.